INTERNATIONAL CONFLICTS AND ECONOMIC GROWTH: The Case of Turkey - Doğan, Cem; Arslan, Ünal; Karmelikli, Hüseyin (Advances in Social Sciences Research Journal, 2016)
In this paper, we examined the asymmetric relationship between international conflicts and economic growth and found that in the long-run and short-run there is not any asymmetry in this subject. We also found that growth rate should be tested with structural breaks because of some structural changes in Turkish economic performance. Our analysis indicate that there is a long-run and symmetric relationship between international conflict and economic growth in Turkey. As we looked at the long-run multiplier of our model, it is an important finding about international conflict. Any increases in international conflict causes negative effect on growth in the long-run. Also with a seeing at a glance to short-run model, we discover that main effect of short-run shocks would be absorbed in model. And approximately 66% of shocks would be corrected each year. So we can conclude that international conflict have negative impact on growth at long-run and economic system of Turkey could adapt with external shocks very quickly.